Las habilidades blandas y la efectividad del talento humano en la base organizacional de una empresa constructora de mediana envergadura. (2022)
This research seeks to establish the main characteristics of the entrepreneurial culture, in the organizational base of the construction sector; from its identification and classification of soft skills, to the recognition of these; promoting the effectiveness of human talent, labor quality and consolidating an entrepreneurial culture in medium-sized organizations in Colombia. In the first instance, the current state of a work will be diagnosed and evaluated quantitatively, allowing to identify the shortcomings and virtues of the human talent; handling concepts such as: organizational structure, work environment, occupational safety, competitiveness, efficiency, effectiveness, productivity, among others; so that from this, the causes that originate the problem of study of our research will be established.